The Role of Sports Motivation and Social Support as Determining Factors of Students' Sports Achievement in Sports Education Learning - Amalya Nadhira Hiesan; Reni Silviah (Siber Nusantara Review, 2025)
The role of sports motivation and social support as determining factors for student sports achievement in sports education learning is a scientific article with the aim of analyzing whether sports achievement plays a role in sports motivation and social support. Qualitative method with a phenomenological approach, the phenomenological approach emphasizes the description of the subject's life experience from the participant's own perspective (phenomenology as a social research method). The results of this article are: 1) Sports motivation plays a role in improving sports achievement, 2) Social support plays a role in improving sports achievement. Apart from these 3 exogenous variables that influence endogenous variables of sports achievement, there are many other factors including teacher competence, teacher leadership, and training consistency.